The double materiality principle and the sustainability reporting practices of Polish listed companies from the WIG30 Index - Małgorzata Macuda; Katarzyna Kobiela-Pionnier (Zeszyty Teoretyczne Rachunkowości)
Purpose: The purpose of the paper is to investigate whether Polish issuers applied the double materiality principle when preparing their reports before implementation of the Corporate Sustainability Reporting Directive (CSRD) became mandatory, and if so, whether they disclosed the double materiality assessment process and at what level. Methodology/approach: The research sample consists of the 30 largest Polish companies listed on the Warsaw Stock Exchange (WIG30 Index). The qualitative content analysis and document analysis of their ESG/CSR/sustainable/non-financial reports for the year 2023 were applied. Findings: Seven companies (23%) already conducted double materiality assessment in accordance with the new EU regulations. Of this group, only one company made full required disclosures, which in the case of the planned preparation of an ESG report in the digital ESEF format would also allow it to perform full tagging with the ESRS XBRL taxonomy. The remaining six companies included four out of the eight mandatory aspects in their double materiality assessment process, as specified in ESRS 2. Three companies (10%) indicated that they had started the double materiality assessment process and described what was done in 2023 and what is planned for the next year. The majority (20 companies; 67%) continued their existing approach to materiality in accordance with the Non-Financial Reporting Directive (NFRD). Research limitations/implications: The research sample was limited to the 30 largest companies listed on the regulated market in one country. Originality/value: The study contributes to the growing literature on the double materiality approach as the basis for sustainability disclosures by offering empirical insights into how Polish listed companies actually apply the double materiality principle in sustainability reporting. The analysed companies were categorised into four groups: Early birds, Seekers, Claimers, and Deadline-driven adopters. Within the first group, differences in the level of double materiality disclosures were noticed and a leading company was identified. Its disclosures were assessed in the context of the planned ESRS XBRL taxonomy.